Financial Strategy for Successful Management of Minikitchen Restaurant using Cash Flow Management - H. Umar (Sean Institute, 2024)
Effective cash flow management will help restaurants to ensure the availability of sufficient funds for daily operations and future business growth, so a financial strategy is needed in managing Minikitchen restaurants using cash flow management. This study applies qualitative methods to help Minikitchen Restaurants implement revenue management strategies, appropriate pricing, SWOT analysis, and careful inventory management. The results of the study indicate that there are several financial strategies that can be applied for the success of Minikitchen restaurant management including preparing a realistic financial budget, managing cash flow effectively, improving understanding and skills in financial management, creating competitive advantages, and adapting to changes in the digital era.